The Linear Elliptic - Surfaces of Revolution - Tatiana Olejnikova (Communications - Scientific letters of the University of Zilina, 2007)
The paper presents a category of revolution surfaces which may be generated by the metrical Euclidean transformation compounded by revolutions and displacements. These surfaces are created by a straight line revolution around a revolution axis moving on an ellipse. This surface group is classified according to the relative positions of a revolution axis moving in contact with an ellipse, and according to the relative positions of a straight line and a revolution axis . The straight line revolution and axis motion can be for equal or different orientation and both can have equal or different radian frequencies. The transformation matrices for the vector equations of the surface and also some properties of these surfaces are presented in this paper.